(untitled) (PerCursos, 2023)
This article deals with the work of the Covid-19 Observatory, a project of the Presidency of Fiocruz and a catalyst in the production and dissemination of information on the pandemic in Brazil. Its activities resulted in the constitution of a digital archive, associated with the idea of "project memory," whose characteristics derived from the health emergency scenario we are of interested in investigating. The general objective of this article is to reflect on the creation and operation of the Covid-19 Observatory with a focus on the challenges related to the management of documents and information from its actions. To this end, concepts from the fields of information science, archival science, social memory and history of sciences and health are used as theoretical inputs, in addition to information from interviews and documentary sources. The results indicate that the health emergency had an impact on various aspects of the production, management, processing, and preservation of the archive.